Gene-Editing: Interpretation of Current Law and Legal Policy - Kim, Na-Kyoung (Dev Reprod, 2017)
With the development of the third-generation gene scissors, CRISPR-Cas9, concerns are being raised about ethical and social repercussions of the new gene-editing technology. In this situation, this article explores the legislation and interpretation of the positive laws in South Korea. The BioAct does not specify and regulate 'gene editing' itself. However, assuming that genetic editing is used in the process of research and treatment, we can look to the specific details of the regulations for research on humans as well as gene therapy research in order to see how genetic editing is regulated under the BioAct. BioAct differentiates the regulation between (born) humans and embryos etc. and the regulation differ entirely in the manner and scope. Moreover, due to the fact that gene therapy products are regarded as drugs, they fall under different regulations. The Korean Pharmacopoeia Act put stringent sanctions on clinical trials for gene therapy products and the official Notification "Approval and Examination Regulations for Biological Products, etc." by Food and Drug Safety Administration may be applied to gene editing for gene therapy purposes.